Pengaruh Pengeluaran Pemerintah, Investasi Publik, Produk Domestik Regional Bruto Terhadap Pendapatan Asli Daerah Kabupaten Aceh Barat - Alisman; Ummu Hanif; Dedi Sufriadi (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2022)
This study aims to analyze government spending, public investment, Gross Regional Domestic Product (GRDP) on Regional Original Income (PAD) in West Aceh District in the period 2005-2018. The analysis model used is multiple linear regression by testing the classical assumptions, namely; normality test, multicorrelation test, heterocidity test, autocorrelation test, correlation coefficient (R), coefficient of determination (R Adjusted), F test, and t test. the calculation uses Software Statistical Product and Service Solutions (SPSS). Based on the results of the study, it was obtained that the variables of government spending (X1), public investment (X2) and GRDP (X3) had a positive and significant effect on Regional Original Income (Y) of West Aceh Regency. Some of the suggestions that are expected are to become a concern for the West Aceh District Government to further increase the allocation of development expenditures in order to be able to stimulate regional economic growth. The West Aceh District Government also needs to measure the increase in PAD with its role in regulating the community's economy so that it can develop more, which in turn can improve the welfare of the people in West Aceh. In addition, the West Aceh District Government also needs to increase investment to invite investors to invest so that with many investors it is hoped that it will increase and impact the people of West Aceh and the community can live productive lives.